Pendidikan Kontrasepsi Pada Wanita Pasangan Usia Subur Sebagai Upaya Antisipasi Baby Bomming Di Masa Adaptasi Kebiasaan Baru Pasca Pandemi Covid-19 Di Wilayah Kecamatan Kuta Utara - Ni Made Rai Widiastuti; Kadek Widiantari (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2021)
The results of family planning services during the COVID-19 pandemic in national scale has decreasedin the number of contraceptive uses reaching 40% in almost all regions in Indonesia (BKKBN, 2020). This couldbe caused by various problems, including an increase in the number of unwanted pregnancies and baby booms orincrease of birth rate. This is due to the obstruction of access to services, delaying access to health facilities dueto fears of contracting COVID-19 and increasing of husband and wife sexual intercourse without usingcontraceptives that inducing pregnancy. Based on the results of Widiastuti's research in 2020, where a survey wasconducted to find out the description of family planning use during the pandemic in the North Kuta District, it wasfound that half of them (53.2%) of respondents were using contraceptives and almost half of them (46.8%) ofrespondents did not use contraception. One of the efforts to suppress the surge in baby births is through the FamilyPlanning program for couples of childbearing age. The aim of this community service is to provide knowledgeabout contraceptive tools and methods in suppressing the surge in baby births. The targets are women ofchildbearing age aged 15-45 years who have not used contraception or who use and do not make repeat visits asmany as 30 people. The implementation of the activity was carried out by assessing the level of understanding ofthe respondents by pre-testing through google forms, implementing counseling, family planning counseling andintroduction of contraceptives and evaluating the material by post-testing via google forms. The results of theactivity show that there is an increase in mother's knowledge about family planning tools and methods, which isexpected to influence the behavior of woman in using contraceptives so that they are expected to anticipate theoccurrence of baby boom.